Conflictos del gas y su gobernanza: el caso de los guaraníes de Tarija, Bolivia. - Perreault, Thomas (2010)
This article examines the implications of natural gas developmentfor Guaraní indigenous communities in southeastern Bolivia. Duringthe 1990s, the Bolivian government enacted a series of neoliberalreforms designed to attract international investment for natural gasand petroleum exploitation and to facilitate the export of hydrocarbons.Protests over the management and distribution of the benefitsderived from natural gas contributed diretly to the election of EvoMorales, Bolivia´s first indigenous president. Nevertheless, anddespite the pro-indigenous discourse of Morales and his MAS (Movementto Socialism) party, gas production has had negative effectsfor indigenous peoples in Bolivia´s Chaco region, who are directlyimpacted by extractive activities. This article examines the case ofthe Guaraní people of the Tierra Comunitaria de Orígen (OriginaryCommunal Land, TCO) Itika Guasu, in Tarija department, whereRepsol´s Margarita ´mega-field´ is located. It is argued here thatgas exploitation in Guaraní territory has been conducted withoutadequate prior consultation or meaningful participation of thepopulations affected.